Troponin through the looking-glass: emerging roles beyond regulation of striated muscle contraction - Johnston, Jamie R. (Oncotarget, 2017)
Troponin is a heterotrimeric Ca(2+)-binding protein that has a well-established role in regulating striated muscle contraction. However, mounting evidence points to novel cellular functions of troponin, with profound implications in cancer, cardiomyopathy pathogenesis and skeletal muscle aging. Here, we highlight the non-canonical roles and aberrant expression patterns of troponin beyond the sarcomeric milieu. Utilizing bioinformatics tools and online databases, we also provide pathway, subcellular localization, and protein-protein/DNA interaction analyses that support a role for troponin in multiple subcellular compartments. This emerging knowledge challenges the conventional view of troponin as a sarcomere-specific protein exclusively involved in muscle contraction and may transform the way we think about sarcomeric proteins, particularly in the context of human disease and aging.